Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.

A quadratic sequence begins:
[tex]\[ 8, \quad 11, \quad 16, \quad 23, \quad 32, \quad \ldots \][/tex]

a) What is the [tex]\( n^{\text{th}} \)[/tex] term rule for this sequence?


Sagot :

To find the [tex]\( n^{\text{th}} \)[/tex] term rule for the given quadratic sequence [tex]\( 8, \, 11, \, 16, \, 23, \, 32, \, \ldots \)[/tex], follow these steps:

1. Identify the First Differences:
[tex]\[ \begin{align*} \Delta_1 & = 11 - 8 = 3 \\ \Delta_2 & = 16 - 11 = 5 \\ \Delta_3 & = 23 - 16 = 7 \\ \Delta_4 & = 32 - 23 = 9 \\ \end{align*} \][/tex]
These are the first differences of the sequence.

2. Identify the Second Differences:
[tex]\[ \begin{align*} \Delta^2_1 & = 5 - 3 = 2 \\ \Delta^2_2 & = 7 - 5 = 2 \\ \Delta^2_3 & = 9 - 7 = 2 \\ \end{align*} \][/tex]
Since the second differences are constant (all equal to 2), the sequence is quadratic.

3. Assume the General Form of the Quadratic Sequence:
The general form of the [tex]\( n^{\text{th}} \)[/tex] term of a quadratic sequence is:
[tex]\[ a n^2 + b n + c \][/tex]

4. Set Up Equations Using Known Terms:
Substitute the first few terms to find [tex]\( a \)[/tex], [tex]\( b \)[/tex], and [tex]\( c \)[/tex]:
[tex]\[ \begin{align*} \text{For } n = 1: & \quad a(1)^2 + b(1) + c = 8 \\ \text{For } n = 2: & \quad a(2)^2 + b(2) + c = 11 \\ \text{For } n = 3: & \quad a(3)^2 + b(3) + c = 16 \\ \end{align*} \][/tex]
This results in the following system of equations:
[tex]\[ \begin{align*} a + b + c &= 8 \quad \text{(i)} \\ 4a + 2b + c &= 11 \quad \text{(ii)} \\ 9a + 3b + c &= 16 \quad \text{(iii)} \\ \end{align*} \][/tex]

5. Solve the System of Equations:
Subtract equation (i) from equation (ii) to eliminate [tex]\( c \)[/tex]:
[tex]\[ (4a + 2b + c) - (a + b + c) = 11 - 8 \\ 3a + b = 3 \quad \text{(iv)} \][/tex]

Similarly, subtract equation (ii) from equation (iii):
[tex]\[ (9a + 3b + c) - (4a + 2b + c) = 16 - 11 \\ 5a + b = 5 \quad \text{(v)} \][/tex]

Subtract equation (iv) from equation (v):
[tex]\[ (5a + b) - (3a + b) = 5 - 3 \\ 2a = 2 \\ a = 1 \][/tex]

Substitute [tex]\( a = 1 \)[/tex] into equation (iv):
[tex]\[ 3(1) + b = 3 \\ 3 + b = 3 \\ b = 0 \][/tex]

Substitute [tex]\( a = 1 \)[/tex] and [tex]\( b = 0 \)[/tex] into equation (i):
[tex]\[ 1 + 0 + c = 8 \\ c = 7 \][/tex]

6. Write the Final [tex]\( n^{\text{th}} \)[/tex] Term Rule:
So, the [tex]\( n^{\text{th}} \)[/tex] term of the sequence is:
[tex]\[ n^2 + 7 \][/tex]

Therefore, the [tex]\( n^{\text{th}} \)[/tex] term rule for the given quadratic sequence is:
[tex]\[ n^2 + 7. \][/tex]
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.